28.2k views
2 votes
Use the recursive formula f(n) = 0.4 . f(n-1) + 12 to determine the 2nd term if f(1) = 4.

A. f(2) = 12.6
B. f(2) = 13.2
C. f(2) = 13.6
D. f(2) = 14.2

2 Answers

1 vote

Answer:

13.6 (Answer C)

Explanation:

I think you meant f(n) = 0.4 * f(n-1) + 12, where * represents multiplication.

Then f(2) = 0.4 * (4) + 12, or 1.6 + 12, or 13.6.

User Jonas Wilms
by
5.5k points
2 votes

Answer:

Assuming you have
f(n)=0.4f(n-1)+12 with
f(1)=4, the answer is f(2)=13.6.

Explanation:

I think that says
f(n)=0.4f(n-1)+12 with
f(1)=4.

Now we want to find
f(2) so replace n with 2:

This gives you:


f(2)=0.4f(2-1)+12


f(2)=0.4f(1)+12


f(2)=0.4(4)+12


f(2)=1.6+12


f(2)=13.6

User Barkley
by
5.0k points